2011
DOI: 10.1007/s00204-010-0642-5
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and intracellular localization of submicron and nano-sized SiO2 particles in HeLa cells

Abstract: Engineered amorphous silica nanoparticles (SiO(2)-NPs) are widely used in dyes, varnishes, plastics and glue, as well as in pharmaceuticals, cosmetics and food. Novel composite SiO(2)-NPs are promising multifunctional devices and combine labels for subsequent tracking and are functionalized e.g. to specifically target cells to deliver their cargo. However, biological and potential toxic effects of SiO(2)-NPs are insufficiently understood. The aim of this study was to determine the uptake and fate of SiO(2)-NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 47 publications
12
81
0
1
Order By: Relevance
“…2, A and B). No colocalization of internalized SiNPs with the Golgi complex, mitochondria, or the endoplasmic reticulum was detected (data not shown), in agreement with Al-Rawi et al (27). The accumulation of SiNPs in late endosomes/lysosomes was also observed in living cells incubated with LysoTracker Red (Fig.…”
Section: Resultssupporting
confidence: 90%
“…2, A and B). No colocalization of internalized SiNPs with the Golgi complex, mitochondria, or the endoplasmic reticulum was detected (data not shown), in agreement with Al-Rawi et al (27). The accumulation of SiNPs in late endosomes/lysosomes was also observed in living cells incubated with LysoTracker Red (Fig.…”
Section: Resultssupporting
confidence: 90%
“…As previously mentioned, this is due to the good colloidal stability the SiO 2 NP dispersion in cell culture media during the exposure periods. Similarly, SiO 2 NPs with core sizes of 70, 200, and 500 nm were reported as nontoxic to HeLa cells in the presence of serum (22,23), which is in good agreement with the observation in this study. Thus, for these (6) SiO 2 30 , (6) SiO 2 200 , and (6) SiO 2 300 NPs, these nontoxic conditions (exposure time: 3 h, dose: 0-500 lg/mL) were chosen for the following FCM, TEM, and XRF experiments.…”
Section: Mtt Cell Viability Assay Of Hela Cells Exposed To Sio 2 Npssupporting
confidence: 92%
“…In addition, as can be seen in Figures 5 and 6, the SiO 2 NPs were not found in the cell nucleus under any of the conditions tested (i.e., different size and surface charge), which is in good agreement with the previous reports. Al-Rawi et al reported that 300 nm SiO 2 NPs were observed in lysosomes and cytoplasm but not in the nucleus, and fluorescence microscopy study with fluorescent-SiO 2 showed no evidence of nuclear translocalization (22,26).…”
mentioning
confidence: 99%
“…QDs which could not enter nuclear membrane is localized only inside cytosol membrane [35]. The same nanoparticles such as silica nanoparticles (SiO 2 ) with diverse type of energy transfer cassettes can localize in different organelles [36]. The interactions between specific nanoparticles and organelles and the effect triggered by such interactions are presented in Table 2.…”
Section: Hepatocytesmentioning
confidence: 99%